The p53 Signalling Pathway in Cutaneous Basal Cell Carcinoma: An Immunohistochemical Description - Shin-Taek Oh; Alexandra Stark; Joerg Reichrath (Medical Journals Sweden, 2020)
Abstract is missing (Short communication)